1999
DOI: 10.1080/000368499323067
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the importance of health and nutrition related factors on food demand: a variable preference investigation

Abstract: The importance of health/nutrition related factors and demographics on food consumption is assessed based on consumer demand using a variable preferences approach. Results of the models show that diet-disease, individual's race, region of residence, urbanization, education, and perceived importance of taste influence the consumption of various food groups. Economic and policy implications of the results are discussed in the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Chi-square value for the effect of age on nutrition knowledge was also significant (p ≤ 0.008 and χ 2 = 13.78). Similar result was reported by Tepper and Rosenzweig, (1999) who indicated there is a positive relationship between age and fruit and vegetable consumption and a negative relationship between age and sugar and sweets consumption. These results are different from those reported by Mansour and Hassan (1994) who reported that the chi square value for the effect of age on knowledge was insignificant in Saudi Arabia.…”
Section: Changes Of Eating Patternssupporting
confidence: 88%
“…Chi-square value for the effect of age on nutrition knowledge was also significant (p ≤ 0.008 and χ 2 = 13.78). Similar result was reported by Tepper and Rosenzweig, (1999) who indicated there is a positive relationship between age and fruit and vegetable consumption and a negative relationship between age and sugar and sweets consumption. These results are different from those reported by Mansour and Hassan (1994) who reported that the chi square value for the effect of age on knowledge was insignificant in Saudi Arabia.…”
Section: Changes Of Eating Patternssupporting
confidence: 88%
“…Low SES, among other factors, can be predictive of lower than adequate purchase/intake of fruits and vegetables (17,18,20,111). Other studies have shown that both low income and low educational attainment have similar effects on food consumption, and have been associated with lower consumption (15,22,34,112,113) and reduced purchasing (41, 114, 115) of vegetables compared to high-income counterparts. Therefore, to further dissect the consumer expenditure patterns as a function of SES, the consumer population was divided into two groups, low-vs. high-income, and analyses were (3) fresh prepared: including all types of salad (e.g., store-prepared salads or manufacturer-prepared salads), as well as appetizers or small plates prepared with vegetables;…”
Section: Analytical Results-overall Samplementioning
confidence: 99%
“…In both cases, the perceived probability of a harm is arguably low in the United States, but for different reasons. This simple framework suggests that, when specifying theoretical models relating to harms, researchers should recognize risk perceptions, how they are structured, their potential changes over time, as well as consumer demographic variables (see Tepper and Rosenzweig (1999), Messer et al (2011) and Piggott and Marsh (2004) for examples of this type of specification).…”
Section: Further Discussion: Theoretically Specifying Market Reacmentioning
confidence: 99%